2004
DOI: 10.1021/bm0499334
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of Aliphatic Homopolyesters and Aliphatic−Aromatic Copolyesters by Anaerobic Microorganisms

Abstract: The anaerobic degradability of natural and synthetic polyesters is investigated applying microbial consortia (3 sludges, 1 sediment) as well as individual strains isolated for this purpose. In contrast to aerobic conditions, the natural homopolyester polyhydroxybutyrate (PHB) degrades faster than the copolyester poly(hydroxybutyrate-co-hydroxyvalerate) (PHBV). For the synthetic polyester poly(epsilon-caroplacton) (PCL), microbial degradation in the absence of oxygen could be clearly demonstrated; however, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
53
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(59 citation statements)
references
References 51 publications
5
53
0
1
Order By: Relevance
“…Polyhydroxybutyrate (PHB) bioplastic is biodegraded in aerobic and anaerobic engineered processes as well as natural environments; however anaerobic co-digestion of PHB for the express purpose of waste management and renewable energy has not been investigated (Abou-Zeid et al, 2004;Volova et al, 2010;Gómez and Michel, 2013;Deroiné et al, 2014). Budwill et al (1996) reported that PHB is anaerobically biodegradable in various scenarios but suggested that municipal anaerobic sewage sludge digesters were suitable PHB degrading environment to generate biomethane.…”
Section: Introductionmentioning
confidence: 99%
“…Polyhydroxybutyrate (PHB) bioplastic is biodegraded in aerobic and anaerobic engineered processes as well as natural environments; however anaerobic co-digestion of PHB for the express purpose of waste management and renewable energy has not been investigated (Abou-Zeid et al, 2004;Volova et al, 2010;Gómez and Michel, 2013;Deroiné et al, 2014). Budwill et al (1996) reported that PHB is anaerobically biodegradable in various scenarios but suggested that municipal anaerobic sewage sludge digesters were suitable PHB degrading environment to generate biomethane.…”
Section: Introductionmentioning
confidence: 99%
“…Reports suggest that PHBV degrades more rapidly than PHB under aerobic conditions [76][77][78]. However, the opposite effect was reported by Abou-Zeid et al [79,80] when running tests under anaerobic conditions. The biodegradability of PHAs containing layered silicates as nano-additives has been investigated with indications that biodegradation rate is decreased under such circumstances.…”
Section: Biodegradabilitymentioning
confidence: 93%
“…It is well known that the degradation pathways and kinetics of synthetic organic compounds largely depend on the conditions (aerobic or anaerobic) under which the wastewater bacteria are striving. For instance, synthetic polyesters have been reported to display higher degradation rates under aerobic conditions than under anaerobic ones [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%